Training Module of Learning Management in the Education 4.0 System - Mushlihatun Syarifah; Yari Dwikurnaningsih (Universitas Pendidikan Ganesha, 2022)
21st-century skills are essential to master. Therefore, we must implement the Education 4.0 system in learning activities. The Indonesian government redesigned a new curriculum (K13) and assigned various policies to support this implementation. However, the results are different than expected. This study aims to analyze the K13 training program, including the modules’ weaknesses, and develop a module learning management module in the Education 4.0 system to support the K13 training program. The method used is research and development with the ADDIE model procedure. The subjects of this research are 30 teachers in one district. The techniques to collect data are interviews, questionnaires, and tests. The data were analyzed using a qualitative and quantitative approach. The research findings show that implementing of K13 training is better from year to year. Still, found module weaknesses in Education 4.0, active learning and educational technology integration, and the learning management concept. Developed a module to fill these weaknesses, results show that the module improves teacher competency in learning management in the Education 4.0 system. The average score improved from 33.33 to 68.70; the number of participants who passed the test increased to 73%. The participants’ average response is 97%, following the expert’s.